KOSAKATA TUMBUHAN OBAT TRADISIONAL MASYARAKAT DAYAK MUALANG - Daniati, Nia; Madeten, Sisilya Saman; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractDayak Mualang Language is one of the regional languages in West Kalimantan, especially Sekadau Regency. The Dayak Mualang community, especially in Seburuk village, Belitang Hulu Subdistrict, still use plants that live wild in the forest as ingredients of traditional medicines which are based on local culture, so that the vocabulary names of traditional medicinal plants need to be preserved and inventoried so that plant vocabulary is not extinct and remains useful for the community. researchers use descriptive methods and qualitative research forms. This research succeeded in gathering 69 vocabularies of traditional medicinal plants. Research on the vocabulary of traditional medicinal plants is very interesting to do, because by researching this can add to the treasury about plants, especially traditional medicinal plants.Â Keywords: Vocabulary, Traditional Medicinal Plants, Dayak MualangÂ